2013
DOI: 10.1002/aoc.3049
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide/oleic acid nanoparticles with immobilized organosilicon derivatives of N‐(2‐hydroxyethyl)tetrahydroisoquinoline: synthesis, morphology and interaction with normal and tumour cells

Abstract: a Superparamagnetic iron oxide/oleic acid nanoparticles bearing lipid-like organosilicon N-(2-hydroxyethyl)-1,2,3,4-tetrahydroisoquinoline derivatives have been synthesized with the aim of their potential biomedical application. X-ray diffraction analysis, Dynamic light-scattering measurements, method of magnetogranulometry and some others have been employed to investigate the morphology and properties of the nanoparticles synthesized. The magnetic core diameter of mixed covered nanoparticles ranged between 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Superparamagnetic iron oxide nanoparticles are biocompatible and have been extensively studied for biomedical applications, as they can offer a high potential in magnetic resonance imaging (MRI), drug delivery, hyperthermal therapies, and bio-separation, among others. These applications benefit from superparamagnetism due to the magnetization generated in the presence of an external magnetic field, and its disappearance when the field is turned off, making it one of the most promising possibilities for use in these biomedical purposes. , Nanoparticles, due to their large surface-to-volume ratio, need appropriate surface functionalization to avoid colloidal instability and, to this end, oleic acid (OA) represents a widely studied biomolecule that offers a highly stable surface coating for magnetite (Fe 3 O 4 ) nanoparticles. OA can interact through chelating chemisorption between the COO – group of carboxylic acid and the iron atom; moreover, if OA is present as a monolayer over the nanoparticle surface, it imparts hydrophobic characteristics because the hydrocarbon chains are located pointing toward the outside. , In addition, OA has been reported as a lipid having a positive fusogenic activity, which is capable of promoting the fusion of liposomes and red blood cells. ,, Regarding the differences between carboxylic acids that act as fusogenic agents and those that are unable to promote fusion, it was proposed that the fusogenic ones tend to have a lower melting temperature than those that are non-fusogenic, and this has led to the proposal that lipids which can induce fusion increase the “fluidity” of the plasma membrane. Dissimilarities have also been observed in the interaction of fusogens and non-fusogenic carboxylic acids with phospholipids in monomolecular films. , Carboxylic acids that possess fusogenic activity exhibit deviations from the ideal behavior when mixed with monolayers of phosphocholine lipids, while such deviations are not observed with non-fusogenic carboxylic acids. , In our previous work related to the study of monolayer mixing behavior of different choline phospholipids with hydrophobic magnetite nanoparticles coated with oleic acid (MNP-OA), we observed that the nanoparticles behaved in a similar way to that of OA, and this allowed us to envisage a possible activity of MNP-OA as fusogens …”
Section: Introductionmentioning
confidence: 99%
“…Superparamagnetic iron oxide nanoparticles are biocompatible and have been extensively studied for biomedical applications, as they can offer a high potential in magnetic resonance imaging (MRI), drug delivery, hyperthermal therapies, and bio-separation, among others. These applications benefit from superparamagnetism due to the magnetization generated in the presence of an external magnetic field, and its disappearance when the field is turned off, making it one of the most promising possibilities for use in these biomedical purposes. , Nanoparticles, due to their large surface-to-volume ratio, need appropriate surface functionalization to avoid colloidal instability and, to this end, oleic acid (OA) represents a widely studied biomolecule that offers a highly stable surface coating for magnetite (Fe 3 O 4 ) nanoparticles. OA can interact through chelating chemisorption between the COO – group of carboxylic acid and the iron atom; moreover, if OA is present as a monolayer over the nanoparticle surface, it imparts hydrophobic characteristics because the hydrocarbon chains are located pointing toward the outside. , In addition, OA has been reported as a lipid having a positive fusogenic activity, which is capable of promoting the fusion of liposomes and red blood cells. ,, Regarding the differences between carboxylic acids that act as fusogenic agents and those that are unable to promote fusion, it was proposed that the fusogenic ones tend to have a lower melting temperature than those that are non-fusogenic, and this has led to the proposal that lipids which can induce fusion increase the “fluidity” of the plasma membrane. Dissimilarities have also been observed in the interaction of fusogens and non-fusogenic carboxylic acids with phospholipids in monomolecular films. , Carboxylic acids that possess fusogenic activity exhibit deviations from the ideal behavior when mixed with monolayers of phosphocholine lipids, while such deviations are not observed with non-fusogenic carboxylic acids. , In our previous work related to the study of monolayer mixing behavior of different choline phospholipids with hydrophobic magnetite nanoparticles coated with oleic acid (MNP-OA), we observed that the nanoparticles behaved in a similar way to that of OA, and this allowed us to envisage a possible activity of MNP-OA as fusogens …”
Section: Introductionmentioning
confidence: 99%
“…15 The modifications caused by the presence of long chain alkyl substituents and positively charged nitrogen atoms in the amphiphilic compounds may influence the coordination behaviour of these compounds in their possible reaction with biological nucleophiles and complex molecules, and may affect the adsorption process on the cell surface 16 and on the surface of superparamagnetic nanoparticles aimed for drug delivery application. 17 The opportunity to regulate the lipophilicity and permeability of biologically active compounds by varying their alkyl/acyl group length and number has been realized. 18,19 Structure-activity studies demonstrated that usually, bioactive compounds have an alkyl chain length between 10 and 18 carbon atoms depending on the nature of the polar group and the type of biological action.…”
Section: Introductionmentioning
confidence: 99%